MATERNAL KNOWLEDGE AND MANAGEMENT STRATEGIES FOR DIARRHEAL INFECTIONS IN CHILDREN UNDER FIVE: A STUDY FROM AZARE, BAUCHI STATE - Fatimah , Amina Abubakar; Suleiman , Ibrahim Usman (Research Journal of Health, Medicine and Nursing, 2024)
This study assesses the knowledge levels of mothers regarding diarrhea and their strategies for the prevention and management of diarrhea among children under the age of five. Quantitative research methods were used through purposive study. The study is based on two objective which is to find out the difference between educated and non-educated mothers; the relationship between knowledge and strategies for prevention of diarrheal diseases among under five (5) children in Bauchi State. Literature was reviewed on the Concept and types of Diarrheas; an empirical study was done. The population of the study consists of 792 mothers with under-five years children; data was collected through questionnaire using 5-point likert scale and sample t-test and PPMC was used for data analysis The findings reveal that there is a significant relationship between knowledge and practice of diarrheal management among mothers of under-five children in Azare metropolis, Bauchi State. Mothers employ a variety of preventive and management strategies, including improved hygiene practices, home remedies, and traditional healing methods. However, the study highlights the importance of providing mothers with accurate and evidence-based information on diarrhea prevention and management. The study found out there is significant relationship between Knowledge and practice of management against diarrhea disease and management strategies against diarrheal disease. The study recommends need for targeted educational interventions that empower mothers with the knowledge and skills required to prevent and manage diarrhea effectively. Community-based health programs should focus on disseminating accurate information on exclusive breastfeeding, ORT, and the importance of seeking timely medical care. Additionally, efforts should be made to address the specific challenges faced by mothers in rural and disadvantaged communities.